Optimizing Tesla’s Car Delivery Process - Susanto Susanto (iBuss Management, 2020)
With the worldwide awareness of global warming keeps on increasing, the market of Electric Vehicles become one of the main alternatives for environmentally friendly mode of transportation.  Tesla, Inc. as one of the market leader of Electric Vehicle industry, starts to offer an affordable version of its BEV, Model 3 which attracts a lot of demands. While the product itself attracts a lot of interest, the customer experience process also needs to be improved as well. This project focuses on the car delivery (order-to-delivery) process of Tesla Motors Netherlands B.V. This study aims to give the delivery team the recommendations on how to optimize the car delivery process by increasing its efficiency and effectiveness. This research focuses on the qualitative research and uses qualitative data to support the findings. The findings show that eficiency and effectiveness can be achieved by making changes in internal processes and improving its current customer support through customer service and customer experience. Keyword: Car Delivery, Efficiency, Effectiveness, Order-to-delivery, Battery Electric Vehicle (BEV)